The Effect of Learning Model Based on Problems (PBM) on Student Learning Results Viewed from Creative Minds of Students Thoughts on Basic Competencies In Basic Settings In Settings of Bun Modifications - Pratiwi, Eka Sakti; Munoto, Munoto; Maspiyah, Maspiyah (International Journal for Educational and Vocational Studies, 2020)
The learning model that has been applied to the learning process in schools is a direct teaching model. In this learning model, teachers only provide concepts and students only accept these concepts. Although students have been given the opportunity to ask questions, in reality only a few are doing it. This is because many students do not master the material about the arrangement of the modified bun area, so they are afraid or confused about what will be asked, besides the students are less enthusiastic and less active in the classroom which then results in less optimal student learning outcomes. Because this learning is taught step by step, the demonstration is very dependent on students' observation skills. One alternative learning model that allows the development of students' thinking skills (reasoning, communication, and connections) in solving problems in the learning of the Modified Regional Bun Reorganization is Problem Based Learning (PBM). This type of research used in this study is experimental research with 2x2 factorial design. The sampling technique used in this study is a non-probability sampling (quota sampling). Data collection techniques in this study used tests of thinking ability, performance tests, and observations. The results of the study can be concluded that the use of PBM models is very appropriate to be used to improve student learning outcomes compared to using direct learning models with regard to facilities and infrastructure.